Comparative analysis of the friction coefficient of various airport pavements - Łukasz Semkło; Agata Wróblewska (Przegląd Komunikacyjny)
Abstract: The parameter defined as the coefficient of friction is one of the basic parameters that are responsible for the characteristics of the surface on which vehicles (cars, aircraft) travel. The coefficient of friction is very important as it is responsible for the safety and relia- bility of the pavement. The paper below presents general issues concerning the friction force and its influence on the movement of aircraft on airport pavements. The requirements for the assessment of the friction coefficient were also discussed. Based on the results of tests carried out at four airports, an analysis of the decrease in the value of the friction coefficient was per- formed. Keywords: Friction; Runway; ASFT